Hakikat, Epistimologi Islam, dan Strategi Istinbath Al Ahkam Fikih Arsitektur - Yulianto, Y (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
Architectural Jurisprudence is an important study in Islamic architecture that has not been much developed. Therefore it is necessary to have an in-depth study related to the re-integration of Islamic jurisprudence and architectural science as a total implementation of Islam. This study focuses on the nature, Islamic epistemology, and strategy of istinbath al ahkam fiqh architecture. This literature study research utilizes Azab's thoughts (2012 & 1997), Murobith (2018), and Zarkani (2006) in examining the nature and strategy of istinbath al-ahkam architectural fiqh and using the reasoning of the Islamic epistemology of Al Jabiri (1989) in studying the reasoning of the Islamic fiqh architectural epistemology. Azab's opinion (2012 & 1997), Murobith (2012), Zarkani (2006), and Al Jabiri (1989) were then combined as needed in making the theoretical foundation of architectural fiqh. The results of this study indicate that the nature of architectural fiqh includes definitions, objects of study, originators, and subjects of architectural fiqh. Architectural fiqh is a collection of various fiqh principles that result in the mobility of a city as an effect of contacting every member of the community, the tendency of building architectural forms, and various issues surrounding the building that are presented as a result of the collaboration of fiqh scholars with building practitioners and architecture as a fiqh legal fatwa based on the science of fiqh proposal . Meanwhile, the object of study is the integration of fiqh studies with architecture and building studies. The subject of the study of architecture fiqh is fiqh law as charging legal low or correlative law in the context of a building. Furthermore, the epistemology of Islam in architectural fiqh is part of the bayani reasoning method as well as burhani. Finally, the strategy of istinbath al ahkam fiqh architecture is the Koran, the sunnah nabawiyah, and the principles of fiqh.